The Development of Lesson Plan Using Blended Learning Model at The University of Billfath - Wilujeng Asih Purwani; Anita Rahmah Dewi (Tell : Teaching of English Language and Literature Journal, 2021)
This research is to redesign the Lesson Plan Bahasa Inggris II (English for Chemistry) by using Blended Learning (BL). The purpose of this study is (1) presenting the Blended Learning (BL) learning development process; (2) integrating face-to-face (F2) learning methods with online learning models; and (3) testing the effectiveness of blended learning (BL) in Chemical Education Study Program University of Billfath. The research design used is research and development (R & D) by applying the Addie model with five stages: (1) analyze phase; (2) Design (Design); (3) Development; (4) Implementation; (5) and evaluation (evaluation). The object of the research was the English language course II carried out in the even semester in the Chemical Education Study Program in the Faculty of Teacher Training and Education, University of Billfath. There are two methods in covering blended learning material as outlined in the lesson plan. The expert validity test showed the results, 96% from Lesson Plan experts, LMS expert 85%, 88,2% from English material experts, and 86,7% from Chemistry experts, while 93,2% from learning media experts, and all of them fall into the valid category. Furthermore, the results of this study indicate that 78,54 % this learning gets a valid category from the observer. The implementation of a lesson plan with a blended learning model provides convenience in the learning process. Students have enough time to learn English anytime anywhere with online learning methods and conduct more intensive discussions in face-to-face meetings